Rheumatoid Factor, Complement, and Mixed Cryoglobulinemia - Peter D. Gorevic (Clinical and Developmental Immunology)
Low serum level of complement component 4 (C4) that occurs in mixed cryoglobulinemia (MC) may be due to in vivo or ex vivo activation of complement by the classical pathway. Potential activators include monoclonal IgM rheumatoid factor (RF), IgG antibodies, and the complexing of the two in the cold, perhaps modulated by the rheology and stoichiometry of cryocomplexes in specific microcirculations. There is also the potential for activation of complement by the alternative and lectin pathways, particularly in the setting of chronic infection and immune stimulation caused by hepatitis C virus (HCV). Engagement of C1q and interaction with specific cell surface receptors serve to localize immune complexes (ICs) to the sites of pathology, notably the cutaneous and glomerular microcirculations. Defective or saturated clearance of ICs by CR1and/or Fc receptors may explain persistence in the circulation. The phlogistic potential of cryoprecipitable ICs depends upon the cleavage of complement components to generate fragments with anaphylatoxin or leukocyte mobilizing activity, and the assembly of the membrane attack complex (C5b-9) on cell surfaces. A research agenda would include further characterization of the effector arm of complement activation in MC, and elucidation of activation mechanisms due to virus and viral antigens in HCV infection.